Implementation and Evaluation of a Social Media-Based Communication Strategy to Enhance Employee Engagement: Experiences From a Children's Hospital, Pakistan - Rasheed, Muneera A.; Hookmani, Alma Arshad; Waleed, Sana; Fatima, H. Sundus; Siddiqui, Soha; Khurram, Muhammad; Hasan, Babar S. (Frontiers in Public Health, 2021)
Social media can complement organizational communication strategy which is integral to employee engagement. However, successful case studies which can allow replication are limited. The objective of the study is to describe the design, and implementation evaluation and evaluation of a social-media based communication strategy in a tertiary care hospital in Pakistan. The leadership of the paediatric service line developed an intervention plan to engage the employees with the newly reframed vision reframed its vision to quality care of clinical care services to include improve patient and family experience.part of patient care and services and wanted to communicate it to the employees. It was realized that communication strategy was core to the its operationalization of execution of the intervention plan. The objective of the study is to describe the design, and implementation evaluation and evaluation of the communication strategy and also share lessons learnt for replication and scale-up. An online communication platform, Facebook page was created for all employees of the paediatric service line.and improve connection with the organization. The strategy to influence employees was based on Cialdini’s 6 principles of persuasion. Implementation of the strategy between October 2017 to December 2019 was evaluated for reach, discussion themes and outcomes using the framework by Murdough (2009). Quantitative indicators included: total posts, mean comments and reactions per post. ; mean reactions; mean likes per post, Thematic analyses and qualitatively with each post and its comment evaluated thematically. Posts were qualitatively analyzed with an emergent approach for insights into the discussion. The analysis revealed a total of 9085 posts, mean reactions per post of 8.4 and mean comments 7.2 and active viewership by 90% members on average. In terms of post types, photos were the highest (4779) while videos were the lowest (1163). Qualitative analysis indicated 54% of the posts were of the theme ‘Inspirational and thought-provoking’ while the greatest engagement was generated on the theme ‘Challenges & solution’. The authors conclude that the strategy was successfully implemented to maintain active membership, engage employees in meaningful conversations and have them express intent to execute quality improvement projects.